A revision of the myrmecophilous genus Smilax Laporte (Coleoptera: Staphylinidae: Staphylininae) - Chatzimanolis, Stylianos (Zootaxa, 2016)
The neotropical myrmecophilous genus Smilax is revised and a new species, Smilax deneinephyto Chatzimanolis is described from southern Brazil. Lectotypes are designated for Smilax cyanea Wasmann and Staphylinus pilosus Fabricius. Smilax cyanea is shown to be a junior synonym of Smilax pilosa. A key and illustration of morphological features are provided for the identification of taxa. The types of the two species of Smilax were not available for study even though they are deposited in public museums.